STUDI KOMPERASI PEMEROLAHAN BAHASA DAN PERAN TEKS KEAGAMAAN DALAM PENGEMBANGAN BAHASA - Maimunah Maimunah; Dzulfikar Ziad (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2022)
Language is a human nature tool to communicate with others and to express their feeling, thought and ideas. Lev Vygotsky is one of the prominient psyschologist. According to Vygotsky language has a significant role in human development. Language from the psycholinguist perspective is the ability of humans in understanding the relation between meaning and word. This research aims to answer the questions of how is language acquisition considering social, cognitive, and psychological factors. This research is applying a literature study by analyzing the previous studies. The results of the study are: (1) language acquisition is the ability to link between the phenomenon or an object with the word, (2) the ability to know the relation of words. Those lead to an understanding of the relation between language and the social semiotic. Research also indicated that the teaching of Al-Qur'an has a significant impact to the development of and creative thinking of the learners. Kata Kunci : Language acquisition, psychological, cognitive